Incidence of surgical site infections in a tertiary hospital in Slovenia: Pogostnost pojavljanja okužb kirurške rane v terciarni bolnišnici v Sloveniji - Taskovska, Dragana; Flis, Vojko (Acta Medico-Biotechnica, 2021)
Purpose: Surveillance is an essential element of surgical site infection (SSI) prevention. Few studies have evaluated the long-term effect of these programs in Slovenia. SSIs are among the most commonly reported health care-associated infections, yet there is a paucity of data on SSI from Slovenia. We aimed to determine the incidence of SSI and explore its associated factors at a tertiary hospital in Slovenia. Methods: Direct and indirect surveillance methods, based on European Centre for Disease Control and Prevention guidelines, were used to define SSI. Patients were followed at 30 days and 1 year postoperatively. Demographic and medical data were collected and risk factors were assessed. Risk factors for SSI and the effect of surveillance time on SSI rates were statistically analyzed. Results: Of 8074 patients analyzed, the SSI rate was found to be 0.28%. One of the statistically significant risk factors for SSI included age (average age 66 years vs. 58 years: p=0.0206, t=2.315, p<0.005). Other known risk factors, such as disease severity, presence of drains, history of previous hospitalization, preoperative stay, wound classification, and surgery duration did not influence the outcome in this study. Conclusion: The incidence of SSI at our hospital was lower than reported in many comparable studies. We establish baseline data for targeted implementation strategies to further improve the quality and safety of health care in this and similar hospitals in Slovenia.